The influence of leadership on employees' employability: a bibliometric analysis, systematic literature review, and research agenda - Hoedemakers, Joost; Vanderstukken, Arne; Stoffers, Jol (Frontiers in Psychology, 2023)
Policymakers, researchers, and practitioners have recently begun treating employability—an individual’s ability to possess and continuously adjust and acquire up-to-date competencies, flexibility, adaptability, and openness to change—as crucial to enabling employees to respond to ubiquitous, rapid changes in organizations. Research into ways to enhance employability, particularly through supervisor leadership, which, for example, facilitates training and competence development, has thus grown in popularity. The exploratory quantitative bibliometric analysis reported in this paper corroborates employability’s recent rise in popularity. A systematic literature review on supervisors’ leadership as an antecedent of employability is both evident and timely. This review thus addresses the question of whether a supervisor’s leadership influences employees’ employability, and in which contexts and through which mechanisms it does so. To address this question, we developed a research protocol that began by identifying initial search terms, deciding on inclusion and exclusion criteria, and searching research databases to identify peer-reviewed published English and Dutch empirical articles. The authors independently identified 134 articles, which were included for full text analysis, of which 10 met inclusion criteria. The authors also independently used the forward and backward snowballing technique, which identified 7 additional articles, resulting in 17 articles in total. Most of these articles identified positive relationships among several conceptualizations of supervisor leadership and employee employability, such as transformational leadership and leader-member exchange, and to a lesser extent, servant leadership and perceived supervisor support. This review suggests that such relationships occur across work contexts, such as educational, SMEs, healthcare, and several other industries, and these contexts also vary geographically. These relationships are largely explained using a social exchange perspective, which means that the positive influence of leadership on employability is itself influenced by a two-way social exchange relationship between supervisor and employees. The quality of the dyadic relationship between leader and followers thus determines the extent to which leaders offer valuable resources such as training and feedback, which subsequently enhance employees’ employability. This review demonstrates that investing in supervisors’ leadership is a valuable HRM strategy that fosters employability, and it identifies practical implications that inform policy and practice and sets an agenda for future employability research.